J. Skelly Wright papers - Wright, J. Skelly
Personal and professional correspondence, case files, opinions, memoranda, reports, speeches and writings, financial papers, teaching material, clippings, printed matter, and photographs documenting Wright's legal and judicial career. The bulk of the papers (1948-1986) pertains to his service as judge on the U.S. District Court for the Eastern District of Louisiana (1949-1962), the U.S. Court of Appeals for the District of Columbia (1962-1987), and the Temporary Emergency Court of Appeals of the United States (1981-1987). Includes files on criminal, regulatory, civil rights, and school integration cases (Bush v. Orleans Parish School Board and Hobson v. Hansen), the Watergate burglary cover-up, and John W. Hinckley, Jr.'s arrest for the attempted assassination of President Ronald Reagan. Also includes material on Wright's tenure as a law professor at Loyola University, New Orleans, La. (1951-1961) and his early career as a notary public (1936-1942). Correspondents include Robert Andrew Ainsworth,Jack Bass, Hugo LaFayette Black, Wayne G. Borah, H. Payne Breazeale, John Robert Brown, Benjamin Franklin Cameron, Herbert William Christenberry, Robert Coles, Kenneth Culp Davis, Eberhard P. Deutsch, Susan Estrich, Abe Fortas, G.W. Foster, Jr., John P. Frank, Fred W. Friendly, Joseph C. Hutcheson, J. Edward Lumbard, Sidney C. Mize, Lee Mortimer, Thomas F. Murphy, Frank T. Read, Eugene V. Rostow, Ralph Slovenko, and Simon Ernest Sobeloff.
Federal judge and professor of law. Full name: James Skelly Wright. Born 1911; died 1988.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ainsworth, Robert Andrew, -- 1910-1981 -- Correspondence; Bass, Jack -- Correspondence; Black, Hugo LaFayette, -- 1886-1971 -- Correspondence; Borah, Wayne G., -- 1891-1966 -- Correspondence; Breazeale, H. Payne -- 1886- -- Correspondence; Brown, John Robert, -- 1909- -- Correspondence; Bush, Earl Benjamin -- Trials, litigation, etc; Cameron, Benjamin Franklin, -- 1890-1964 -- Correspondence; Christenberry, Herbert William, -- 1897-1975 -- Correspondence; Coles, Robert -- Correspondence; Davis, Kenneth Culp -- Correspondence; Deutsch, Eberhard P. -- 1897-1980 -- Correspondence; Estrich, Susan -- Correspondence; Fortas, Abe -- Correspondence; Foster, G. W. -- 1919- -- Correspondence; Frank, John P. -- 1917-2002 -- Correspondence; Friendly, Fred W. -- Correspondence; Hansen, Carl F. -- Trials, litigation, etc; Hinckley, John W; Hobson, Julius W. -- Trials, litigation, etc; Hutcheson, Joseph C. -- 1879-1973 -- Correspondence; Lumbard, J. Edward -- 1901- -- Correspondence; Mize, Sidney C. -- 1888-1965 -- Correspondence; Mortimer, Lee, -- 1904-1963 -- Correspondence; Murphy, Thomas F. -- 1905- -- Correspondence; Read, Frank T., -- 1938- -- Correspondence; Reagan, Ronald -- Assassination attempt, 1981.; Rostow, Eugene V. -- 1913-2002 -- Correspondence; Slovenko, Ralph -- Correspondence; Sobeloff, Simon Ernest, -- 1894-1973 -- Correspondence; Loyola University (New Orleans, La.). -- School of Law -- Faculty; Orleans Parish School Board -- Trials, litigation, etc; United States. -- Court of Appeals (District of Columbia Circuit); United States. -- District Court (Louisiana : Eastern District); United States. -- Temporary Emergency Court of Appeals; Administrative agencies; Civil rights; Courts -- Louisiana; Courts -- Washington (D.C.); Criminal law; Judges -- Louisiana; Judges -- Washington (D.C.); Law -- Cases; Law -- Study and teaching -- Louisiana; Notaries -- Louisiana; School integration -- Louisiana; School integration -- Washington (D.C.); Watergate Affair, 1972-1974.; Educators; Jurists